Milling of carbon fibre reinforced polymer (CFRP) using TiAlN coated end mills - Konneh, Mohamed; Sudin, Izman; Abdullah, Kassim Abdulrahman (2014)
This study was undertaken to investigate the influence of machining parameters on delamination of milled 3 mm-thick Carbon Fibre Reinforced Composite (CFRP) using 4 mm-diameter 2-fluted Titanium Aluminium Nitride (TiAlN) coated carbide end mills. Three machining parameters, rotation speed, feed rate and depth of cut were considered. The machining experiments were conducted on a Mikrotool DT-110 CNC micro machine based on Box-Behnken design of experiments and resulted into 17 runs. A DT 2336B Laser Tachometer was used to check the rotational speed prior to any trial run. Optical microscopy examination reveals minimum delamination value 4.05 at the condition of spindle speed (25,000 rpm), depth of cut (50µm) and feed rate (3 mm/min) and the maximum delamination value 5.04 mm at the condition of spindle speed (35000 rpm), depth of cut (150µm) and feed rate (9 mm/min). A mathematical model relating the milling parameters and delamination has been established.